Modified technique of stent fenestration of the atrial septum. Issue 10 (15th September 2003) - Stümper, O; Gewillig, M; Vettukattil, J; Budts, W; Chessa, M; Chaudhari, M; Wright, J G C
Abstract : Objectives: To develop a modified technique for stenting the atrial septum in the treatment of patients with a failing Fontan operation or pulmonary hypertension. Setting: Two tertiary referral centres. Study design: Prospective collaborative clinical study. Patients and methods: A stent was mounted on a standard valvoplasty balloon catheter which was constricted to a predefined diameter by a loop created from a temporary pacing wire. Full balloon inflation created a diabolo shaped stent configuration. The technique was employed in 12 consecutive patients to relieve symptoms of a failing Fontan circulation (n = 6) or severe pulmonary hypertension (n = 6). Results: Ex vivo studies confirmed that a diabolo shaped stent configuration could be achieved using the above technique. Transcatheter stent implantation was successful in all 12 patients. All six Fontan patients showed significant clinical improvement. Right atrial pressure decreased from (mean (SD)) 16.8 (2.5) to 13.7 (1.9) mm Hg (p < 0.05), and arterial oxygen saturation from 92.8 (1.8)% to 82.7 (3.8)% (p < 0.01). Six patients underwent successful stent fenestration for treatment of pulmonary hypertension. All stents were patent and stable at the most recent follow up (mean 1.75 (1.05) years). No early or late stent related complications were encountered. Conclusions: This new technique allows placement of a diabolo shaped stent with a predefined diameter across the atrial septum. The diabolo shape increases stent stability, facilitates recrossing of the stent during future catheter interventions, and ensures medium term stent patency.